Everyday surveillance: vigilance and visibility in postmodern life - Staples, William G. (Rowman & Littlefield, 2014)
Everyday Surveillance is a provocative exploration of the myriad ways we are watched each day -- from internet use to public video cameras -- and how this surveillance shapes our lives. The second edition considers new topics, such as the rise of social media, and updates research throughout. This is an ideal text for introducing students to concepts of social control and provoking discussion. -- Provided by publisher